Heat-conducting silica gel gasket as well as preparation method and application thereof

By using diamond coated with γ-Fe2O3 as the thermal conductivity material, the problem of insufficient high-temperature aging resistance of existing thermally conductive silicone gaskets is solved, and the excellent aging resistance and stable thermal conductivity of thermally conductive silicone gaskets under high temperature conditions is achieved.

CN119684682APending Publication Date: 2025-03-25GUANGZHOU JOINTAS CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411741573.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The high-temperature resistance temperature of existing thermally conductive silicone gaskets is less than 250℃ and the long-term use temperature does not exceed 200℃, making it difficult to meet the high-temperature aging resistance performance of thermally conductive materials in the high-tech field.

Method used

Diamond coated with γ-Fe2O3 is used as the thermal conductivity material, and diamond and γ-Fe2O3 are effectively coated through a specific preparation method to form a synergistic high temperature-resistant thermal conductivity material, and added to the thermally conductive silicone gasket.

Benefits of technology

It significantly improves the aging resistance of thermally conductive silicone gaskets under high temperature conditions, extends the continuous use time of the gaskets, reduces the increase in interface thermal resistance caused by aging, and improves the stability of thermal conductivity and hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting materials, and discloses a heat-conducting silica gel gasket as well as a preparation method and application thereof. The invention relates to a heat conduction material, which is diamond coated with gamma-Fe2O3. The heat-conducting silica gel gasket is prepared from the following raw materials in parts by mass: 90 to 110 parts of vinyl silicone oil, 5 to 25 parts of hydrogen-containing silicone oil, 2000 to 3500 parts of heat-conducting filler, 0.5 to 5 parts of temperature-resistant agent, 0.5 to 10 parts of coupling aid, 0.1 to 5 parts of catalyst, 0.01 to 2 parts of inhibitor and 10 to 100 parts of heat-conducting material. According to the heat-conducting material provided by the invention, the diamond and the gamma-Fe2O3 are taken as raw materials, a synergistic high-temperature-resistant effect is exerted, and the preparation method is simple in step, mild in process condition and easy to realize industrialization; the heat-conducting silica gel gasket has excellent heat-conducting property and high-temperature resistance, the continuous use time of the gasket in a high-temperature oxidation environment can be obviously prolonged, and the application requirements of electronic components can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat-conducting materials, and in particular to a heat-conducting silicone gasket and a preparation method and application thereof. Background Art

[0002] With the rapid development of high-tech fields such as electronics, aviation, communications, and new energy vehicles, versatility and portability have become the main competitive advantages of electronic products, making electronic products gradually develop in the direction of miniaturization, high density, high power, and multi-function. At the same time, it also puts forward higher requirements on the thermal conductivity and high temperature aging resistance of thermal conductive materials.

[0003] Organic silicon rubber uses silicon oxygen bond as molecular skeleton, and forms a network polymer compound through cross-linking of organic groups, which has good high temperature resistance and high decomposition temperature. In addition, the bond energy of silicon oxygen bond is 422.5kJ / mol, which is much higher than carbon oxygen bond (351kJ / mol) and carbon carbon bond (347kJ / mol), so organic silicon rubber has good temperature resistance and aging performance. However, the high temperature tolerance temperature of most existing thermal conductive organic silicon gaskets is less than 250℃, and the long-term use temperature does not exceed 200℃.

[0004] At present, the methods for improving the heat aging resistance of silicone rubber are mainly the following: (1) Main chain modification, by introducing rigid groups such as phenylene and phenylene ether with large steric hindrance into the main chain, the flexibility of silicone rubber is reduced, the rotation of the molecular chain is difficult, the probability of forming π-π bonds between unconnected silicon atoms and oxygen atoms in the main chain is reduced, and the main chain is inhibited from degrading. However, due to the high overall rigidity of the polymer, the difficulty of synthesis and processing technology, the low powder consumption and high cost, this method has a low application prospect; (2) Side chain modification, by introducing phenyl and fluorine-containing groups in the side chain, the silicone rubber can be effectively improved. Heat resistance of organic silicone rubber, but there are also defects such as poor powder absorption and high synthesis cost of the prepared silicone rubber; (3) Adding heat-resistant agent, which can inhibit the degradation of the main chain of silicone rubber and the oxidative cross-linking of the side chain by absorbing free radicals. Commonly used heat-resistant agents are metal oxides such as Fe2O3 and CeO2. They are cheap and widely available, but when used alone, they often do not improve the heat resistance of organic silicone rubber enough. Surface graphene, carbon nanotubes and other materials can also improve the high temperature aging resistance of organic silicone rubber, but due to their conductivity, their application as heat-resistant agents is limited. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a thermally conductive material; the second purpose of the present invention is to provide a method for preparing the thermally conductive material; the third purpose of the present invention is to provide a thermally conductive silicone gasket; the fourth purpose of the present invention is to provide the application of the thermally conductive silicone gasket.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a thermally conductive material, wherein the thermally conductive material is diamond coated with γ-Fe2O3.

[0008] Preferably, in the γ-Fe2O3 coated diamond, the diamond has a particle size of 2-100 μm; further preferably, the diamond has a particle size of 30-60 μm.

[0009] Preferably, in the γ-Fe2O3 coated diamond, the thickness of the γ-Fe2O3 coating layer is 0.01-0.5 μm; further preferably, the thickness of the γ-Fe2O3 coating layer is 0.01-0.2 μm.

[0010] Preferably, the thermally conductive material comprises the following raw materials: diamond, iron salt, acid solution, surfactant, alcohol and alkali solution.

[0011] Preferably, the surfactant is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol; more preferably, the surfactant is polyvinyl pyrrolidone.

[0012] Preferably, the iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric stearate and ferric acetate; more preferably, the iron salt is ferric nitrate.

[0013] Preferably, the mass ratio of diamond, iron salt, surfactant and alcohol is (10-30):(55-75):(0.3-1.5):100; further preferably, the mass ratio of diamond, iron salt, surfactant and alcohol is (10-25):(60-70):(0.3-1):100.

[0014] Preferably, the acid solution includes hydrochloric acid or nitric acid.

[0015] Preferably, the solute concentration of the acid solution is 2-5 mol / L.

[0016] Further preferably, the acid solution comprises hydrochloric acid with a solute concentration of 2-3 mol / L and nitric acid with a solute concentration of 3-5 mol / L.

[0017] Preferably, the solute concentration of the alkali solution is 20-30wt%; further preferably, the solute concentration of the alkali solution is 20-25wt%.

[0018] Preferably, the alkali solution comprises aqueous ammonia.

[0019] Preferably, the alcohol comprises anhydrous ethanol.

[0020] The second aspect of the present invention provides a method for preparing the thermally conductive material according to the first aspect of the present invention, comprising the following steps:

[0021] S1, soaking the diamond in acid solution to obtain activated diamond;

[0022] S2, dispersing iron salt in alcohol, adding the activated diamond and surfactant, and dropping alkali solution for precipitation;

[0023] S3, collecting the precipitate and calcining it to obtain the thermal conductive material.

[0024] Preferably, the step S1 specifically includes the following steps: placing the diamond in 2-3 mol / L hydrochloric acid, ultrasonically dispersing for 20-40 min, filtering, washing until neutral, then placing in 3-5 mol / L nitric acid, magnetically stirring for 1.5-3 h, filtering, washing until neutral, and drying at 90-110° C. for 2-4 h to obtain the activated diamond.

[0025] Preferably, in step S2, after the iron salt is dispersed in alcohol, ultrasonic dispersion is performed for 10-30 minutes; more preferably, ultrasonic dispersion is performed for 15-30 minutes.

[0026] Preferably, in step S2, after adding the activated diamond and the surfactant, magnetic stirring is performed for 30-150 minutes; more preferably, magnetic stirring is performed for 30-120 minutes.

[0027] Preferably, in step S2, the dropping speed of the alkali solution is 0.03-0.15 g / s; further preferably, the dropping speed of the alkali solution is 0.03-0.12 g / s.

[0028] Preferably, in the step S3, after collecting the precipitate, the step further includes washing and drying at 90-110° C. for 2-4 hours.

[0029] Preferably, in step S3, the calcination temperature is 500-700°C; further preferably, the calcination temperature is 550-650°C.

[0030] Preferably, in step S3, the calcination time is 2-10 hours; more preferably, the calcination time is 3-8 hours.

[0031] Preferably, in step S3, the heating rate of the calcination is 10-20°C / min; further preferably, the heating rate of the calcination is 10-15°C / min.

[0032] Preferably, in the step S3, the calcination is performed under a protective atmosphere.

[0033] Preferably, the protective atmosphere includes a nitrogen atmosphere or an inert gas atmosphere, and the inert gas includes argon.

[0034] Preferably, in step S3, after the calcination is completed, the steps of cooling, filtering, washing and drying the product at 90-110° C. for 1.5-4 hours are also included.

[0035] The third aspect of the present invention provides a thermally conductive silicone gasket, which comprises the following raw materials, by mass: 90-110 parts of vinyl silicone oil, 5-25 parts of hydrogenated silicone oil, 2000-3500 parts of thermally conductive filler, 0.5-5 parts of temperature resistant agent, 0.5-10 parts of coupling aid, 0.1-5 parts of catalyst, 0.01-2 parts of inhibitor, and 10-100 parts of the thermally conductive material described in the first aspect of the present invention.

[0036] Preferably, the thermally conductive silicone gasket comprises the following raw materials: 95-105 parts of vinyl silicone oil, 5-20 parts of hydrogenated silicone oil, 2000-3200 parts of thermally conductive filler, 1-3 parts of temperature resistant agent, 5-10 parts of coupling aid, 0.1-1 parts of catalyst, 0.01-1 parts of inhibitor, and 30-60 parts of the thermally conductive material described in the first aspect of the present invention.

[0037] Preferably, the hydrogen content of the hydrogen-containing silicone oil is 0.05-0.3 wt %; further preferably, the hydrogen content of the hydrogen-containing silicone oil is 0.08-0.2 wt %.

[0038] Preferably, the hydrogen-containing silicone oil is selected from at least one of terminal hydrogen-containing silicone oil and terminal side hydrogen-containing silicone oil.

[0039] Preferably, the content of siloxane D3-D20 in the vinyl silicone oil and the hydrogen-containing silicone oil is less than 100 ppm.

[0040] Preferably, the viscosity of the vinyl silicone oil at 23° C. is 100-500 cps.

[0041] Preferably, the particle size (D50) of the thermally conductive filler is in three grades: 0.3-1.5 μm, 3-10 μm and 40-150 μm.

[0042] Preferably, the thermally conductive filler is selected from at least one of diamond, aluminum hydroxide, aluminum oxide, magnesium hydroxide, magnesium oxide, zinc oxide, silicon powder, aluminum nitride, boron nitride, aluminum carbide, silicon carbide, and boehmite.

[0043] Preferably, the temperature resistant agent is selected from at least one of α-Fe2O3, γ-Fe2O3, and CeO2.

[0044] Preferably, the coupling aid is selected from at least one of hexamethyldisilazane, hexamethyldisiloxane, 3-(methacryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyltriethoxysilane, hexadecyltrimethoxysilane, dodecyltrimethoxysilane, n-decyltrimethoxysilane, methyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, stearic acid, oleic acid, lauric acid, and adipic acid; further preferably, the coupling aid includes at least hexamethyldisilazane.

[0045] Preferably, the catalyst comprises a platinum catalyst; the concentration of the catalyst is 3000-5000 ppm.

[0046] Preferably, the inhibitor comprises an alkynol inhibitor.

[0047] Preferably, the thermally conductive silicone gasket is prepared by a method comprising the following steps:

[0048] The vinyl silicone oil, thermal conductive filler, thermal conductive material, temperature resistant agent and coupling aid are mixed at 30-160°C, cooled to 40°C or below, inhibitor and hydrogen-containing silicone oil are added first, and then a catalyst is added to obtain a mixture, and the mixture is calendered to obtain the thermal conductive silicone gasket.

[0049] Preferably, the process of mixing the vinyl silicone oil, thermal conductive filler, thermal conductive material, temperature resistant agent and coupling aid is: first stirring at 30-80°C for 1-5h, then stirring at 90-160°C for 1-5h; further preferably, first stirring at 40-70°C for 1-3h, then stirring at 100-150°C for 1-3h.

[0050] Preferably, after adding the inhibitor and hydrogen-containing silicone oil, stirring is carried out for 20-40 minutes under vacuum.

[0051] Preferably, after adding the catalyst, stirring is carried out for 20-40 minutes under vacuum.

[0052] Preferably, the calendering temperature is 70-160°C; more preferably, the calendering temperature is 80-150°C.

[0053] Preferably, the calendering speed is 0.3-2 m / min; further preferably, the calendering speed is 0.3-1.5 m / min.

[0054] Preferably, the thickness of the thermally conductive silicone gasket is 1-2 mm.

[0055] The fourth aspect of the present invention provides the use of the thermally conductive silicone gasket described in the third aspect of the present invention in electronic components.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1) The heat-conducting material provided by the present invention uses diamond and γ-Fe2O3 as raw materials, and plays a synergistic high-temperature resistance role;

[0058] 2) The preparation method of the thermal conductive material provided by the present invention has simple steps, mild process conditions, and is easy to realize industrialization;

[0059] 3) The heat-conductive silicone gasket provided by the present invention is added with heat-conductive materials, so that the degree of side chain oxidation and main chain debonding hydrolysis under high temperature conditions is greatly reduced, the thermal conductivity and hardness fluctuate less, and the increase in interface thermal resistance caused by aging is reduced, which can significantly extend the continuous use time of the gasket in a high-temperature oxidation environment, effectively improve the high-temperature aging resistance, and save the cost of replacing the gasket;

[0060] 4) The thermally conductive silicone gasket provided by the present invention can meet the application requirements of electronic components, greatly reducing the maintenance and repair frequency of electrical components, and indirectly improving the working efficiency of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a photo of the thermally conductive silicone gasket prepared in Example 1 before aging;

[0062] Figure 2 Photographs of the thermally conductive silicone gasket prepared in Example 1 after aging and folding test;

[0063] Figure 3 A photo was taken of the thermally conductive silicone gasket prepared in Comparative Example 1 after aging and folding test;

[0064] Figure 4 This is a photo of the thermally conductive silicone gasket prepared in Example 2 before aging;

[0065] Figure 5 Take a photo of the thermally conductive silicone gasket prepared in Example 2 after aging and folding test;

[0066] Figure 6 A photo was taken of the thermally conductive silicone gasket prepared in Comparative Example 2 after aging and the folding test. DETAILED DESCRIPTION

[0067] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0068] Example 1

[0069] This embodiment prepares a thermally conductive material, and uses the thermally conductive material as a raw material to prepare a thermally conductive silicone gasket:

[0070] The preparation steps of thermal conductive materials are as follows:

[0071] S11, placing diamond with a particle size of 50 μm in 2 mol / L dilute hydrochloric acid, ultrasonically dispersing for 30 min, filtering, washing with deionized water until neutral, then placing in 3.5 mol / L nitric acid solution with magnetic stirring for 2 h, filtering, washing with deionized water until neutral, and drying in an oven at 100°C for 3 h to obtain activated diamond;

[0072] S21, prepare materials according to the mass ratio of diamond, ferric nitrate, surfactant and alcohol = 10:60:0.3:100, add ferric nitrate into anhydrous ethanol, ultrasonically disperse for 20 minutes to form a ferric nitrate solution, add activated diamond and polyvinyl pyrrolidone, stir at high speed by magnetic force for 80 minutes, and add 25wt% ammonia water dropwise at a speed of 0.08g / s until no flocculent precipitate is produced;

[0073] S31. Let stand to separate the precipitates, collect them by filtration, wash them with deionized water until they are neutral, and then dry them in an oven at 100°C for 3 hours. Then, place them in a muffle furnace and calcine them under argon protection at a temperature of 600°C, a heating rate of 12°C / min, and a calcination time of 5 hours. The product is cooled to room temperature, filtered, washed, and dried in an oven at 100°C for 2 hours to obtain a thermal conductive material I with a coating thickness of 0.03 μm.

[0074] The raw material composition of thermal conductive silicone gasket is shown in Table 1:

[0075] Table 1 Raw material composition of thermal conductive silicone gasket in Example 1

[0076]

[0077]

[0078] The preparation steps of thermal conductive silicone gasket are as follows:

[0079] (1) Add vinyl silicone oil, thermal conductive filler, thermal conductive material I, temperature resistant agent and hexadecyltrimethoxysilane into a reaction kettle, stir at high speed at 40° C. for 1.5 h, then add hexamethyldisilazane, stir at high speed for 1 h, heat to 150° C. and stir at low speed for 2.5 h, cool to 40° C., add inhibitor and hydrogen-containing silicone oil, stir under vacuum for 30 min, then add catalyst, stir under vacuum for 30 min, and obtain thermal conductive silicone gasket material;

[0080] (2) Turn on the thermal calendering line, set the temperature of each section of the tunnel furnace from front to back to 80°C, 100°C, 120°C, 130°C and 120°C, adjust the calendering thickness to 1 mm, and after the tunnel furnace reaches the set temperature, put the high temperature aging resistant thermal conductive gasket material into the calendering line trough, and calender at a speed of 0.5 m / min to obtain a thermal conductive silicone gasket.

[0081] Example 2

[0082] This embodiment prepares a thermally conductive material, and uses the thermally conductive material as a raw material to prepare a thermally conductive silicone gasket:

[0083] The preparation steps of thermal conductive materials are as follows:

[0084] S11, placing diamond with a particle size of 40 μm in 2 mol / L dilute hydrochloric acid, ultrasonically dispersing for 30 min, filtering, washing with deionized water until neutral, then placing in 3.5 mol / L nitric acid solution with magnetic stirring for 2 h, filtering, washing with deionized water until neutral, and drying in an oven at 100°C for 3 h to obtain activated diamond;

[0085] S21, prepare materials according to the mass ratio of diamond, ferric nitrate, surfactant and alcohol = 15:65:0.5:100, add ferric nitrate into anhydrous ethanol, ultrasonically disperse for 20 minutes to form a ferric nitrate solution, add activated diamond and polyvinyl pyrrolidone, stir at high speed by magnetic force for 80 minutes, and add 25wt% ammonia water dropwise at a speed of 0.05g / s until no flocculent precipitate is produced;

[0086] S31. Let stand to separate the precipitates, collect them by filtration, wash them with deionized water until they are neutral, and then dry them in an oven at 100°C for 3 hours. Then, place them in a muffle furnace and calcine them under argon protection at a temperature of 600°C, a heating rate of 12°C / min, and a calcination time of 5 hours. The product is cooled to room temperature, filtered, washed, and dried in an oven at 100°C for 2 hours to obtain a thermal conductive material II with a coating thickness of 0.08 μm.

[0087] The raw material composition of thermal conductive silicone gasket is shown in Table 2:

[0088] Table 2 Raw material composition of thermal conductive silicone gasket in Example 2

[0089]

[0090] The preparation steps of thermal conductive silicone gasket are as follows:

[0091] (1) Add vinyl silicone oil, thermal conductive filler, thermal conductive material II, temperature resistant agent and dodecyl trimethylsiloxane into a reaction kettle, stir at high speed at 40° C. for 1.5 h, then add hexamethyldisilazane, stir at high speed for 1 h, heat to 150° C. and stir at low speed for 2.5 h, cool to 40° C., add inhibitor and hydrogen-containing silicone oil, stir under vacuum for 30 min, then add catalyst, stir under vacuum for 30 min, and obtain thermal conductive silicone gasket material;

[0092] (2) Turn on the thermal calendering line, set the temperature of each section of the tunnel furnace from front to back to 70°C, 90°C, 115°C, 130°C and 115°C, adjust the calendering thickness to 1 mm, and after the tunnel furnace reaches the set temperature, put the high temperature aging resistant thermal conductive gasket material into the calendering line trough, and calender at a speed of 0.5 m / min to obtain a thermal conductive silicone gasket.

[0093] Example 3

[0094] This embodiment prepares a thermally conductive material, and uses the thermally conductive material as a raw material to prepare a thermally conductive silicone gasket:

[0095] The preparation steps of thermal conductive materials are as follows:

[0096] S11, placing diamond with a particle size of 40 μm in 2 mol / L dilute hydrochloric acid, ultrasonically dispersing for 30 min, filtering, washing with deionized water until neutral, then placing in 3.5 mol / L nitric acid solution with magnetic stirring for 2 h, filtering, washing with deionized water until neutral, and drying in an oven at 100°C for 3 h to obtain activated diamond;

[0097] S21, prepare materials according to the mass ratio of diamond, ferric nitrate, surfactant and alcohol = 20:65:0.7:100, add ferric nitrate into anhydrous ethanol, ultrasonically disperse for 20 minutes to form a ferric nitrate solution, add activated diamond and polyvinyl pyrrolidone, stir at high speed by magnetic force for 80 minutes, and add 25wt% ammonia water dropwise at a speed of 0.10g / s until no flocculent precipitate is produced;

[0098] S31. Let stand to separate the precipitates, collect them by filtration, wash them with deionized water until they are neutral, and then dry them in an oven at 100°C for 3 hours. Then, place them in a muffle furnace and calcine them under argon protection at a temperature of 600°C, a heating rate of 12°C / min, and a calcination time of 5 hours. The product is cooled to room temperature, filtered, washed, and dried in an oven at 100°C for 2 hours to obtain a thermal conductive material III with a coating thickness of 0.05 μm.

[0099] The raw material composition of the thermal conductive silicone gasket is shown in Table 3:

[0100] Table 3 Raw material composition of thermal conductive silicone gasket in Example 3

[0101]

[0102] The preparation steps of thermal conductive silicone gasket are as follows:

[0103] (3) Add vinyl silicone oil, thermal conductive filler, thermal conductive material III, temperature resistant agent and dodecyl trimethylsiloxane into a reaction kettle, stir at high speed at 40° C. for 1.5 h, then add hexamethyldisilazane, stir at high speed for 1 h, heat to 150° C. and stir at low speed for 2.5 h, cool to 40° C., add inhibitor and hydrogen-containing silicone oil, stir under vacuum for 30 min, then add catalyst, stir under vacuum for 30 min, and obtain thermal conductive silicone gasket material;

[0104] Turn on the thermal calendering line, set the temperature of each section of the tunnel furnace from front to back to 70℃, 90℃, 125℃, 135℃ and 115℃, adjust the calendering thickness to 1mm, and after the tunnel furnace reaches the set temperature, put the high temperature aging resistant thermal conductive gasket material into the calendering line trough, and calender at a speed of 0.5m / min to obtain the thermal conductive silicone gasket.

[0105] Example 4

[0106] This embodiment prepares a thermally conductive material, and uses the thermally conductive material as a raw material to prepare a thermally conductive silicone gasket:

[0107] The preparation steps of thermal conductive materials are as follows:

[0108] S11, placing diamond with a particle size of 60 μm in 2 mol / L dilute hydrochloric acid, ultrasonically dispersing for 30 min, filtering, washing with deionized water until neutral, then placing in 3.5 mol / L nitric acid solution with magnetic stirring for 2 h, filtering, washing with deionized water until neutral, and drying in an oven at 100° C. for 3 h to obtain activated diamond;

[0109] S21, prepare materials according to the mass ratio of diamond, ferric nitrate, surfactant and alcohol = 25:70:1:100, add ferric nitrate into anhydrous ethanol, ultrasonically disperse for 20 minutes to form a ferric nitrate solution, add activated diamond and polyvinyl pyrrolidone, stir at high speed by magnetic force for 80 minutes, and add 25wt% ammonia water dropwise at a speed of 0.05g / s until no flocculent precipitate is produced;

[0110] S31. Let stand to separate the precipitates, collect them by filtration, wash them with deionized water until they are neutral, and then dry them in an oven at 100°C for 3 hours. Then, place them in a muffle furnace and calcine them under argon protection at a temperature of 600°C, a heating rate of 12°C / min, and a calcination time of 5 hours. The product is cooled to room temperature, filtered, washed, and dried in an oven at 100°C for 2 hours to obtain a thermal conductive material IV with a coating thickness of 0.05 μm.

[0111] The raw material composition of thermal conductive silicone gasket is shown in Table 4:

[0112] Table 4 Raw material composition of thermal conductive silicone gasket in Example 4

[0113]

[0114] The preparation steps of thermal conductive silicone gasket are as follows:

[0115] (1) Add vinyl silicone oil, thermal conductive filler, thermal conductive material IV, temperature resistant agent and n-decyl trimethylsiloxane into a reaction kettle, stir at high speed at 40° C. for 1.5 h, then add hexamethyldisilazane, stir at high speed for 1 h, heat to 150° C. and stir at low speed for 2.5 h, cool to 40° C., add inhibitor and hydrogen-containing silicone oil, stir under vacuum for 30 min, then add catalyst, stir under vacuum for 30 min, and obtain thermal conductive silicone gasket material;

[0116] (2) Turn on the thermal calendering line, set the temperature of each section of the tunnel furnace from front to back to 80°C, 100°C, 125°C, 135°C and 115°C, adjust the calendering thickness to 1 mm, and after the tunnel furnace reaches the set temperature, put the high temperature aging resistant thermal conductive gasket material into the calendering line trough, and calender at a speed of 0.5 m / min to obtain a thermal conductive silicone gasket.

[0117] Example 5

[0118] This embodiment prepares a thermally conductive material, and uses the thermally conductive material as a raw material to prepare a thermally conductive silicone gasket:

[0119] The preparation steps of thermal conductive materials are as follows:

[0120] S11, placing diamond with a particle size of 60 μm in 2 mol / L dilute hydrochloric acid, ultrasonically dispersing for 30 min, filtering, washing with deionized water until neutral, then placing in 3.5 mol / L nitric acid solution with magnetic stirring for 2 h, filtering, washing with deionized water until neutral, and drying in an oven at 100° C. for 3 h to obtain activated diamond;

[0121] S21, prepare materials according to the mass ratio of diamond, ferric nitrate, surfactant and alcohol = 20:63:0.4:100, add ferric nitrate into anhydrous ethanol, ultrasonically disperse for 20 minutes to form a ferric nitrate solution, add activated diamond and polyvinyl pyrrolidone, stir at high speed by magnetic force for 80 minutes, and add 25wt% ammonia water dropwise at a speed of 0.04g / s until no flocculent precipitate is produced;

[0122] S31. Let the mixture stand for stratification, collect the precipitate by filtration, wash it with deionized water until it is neutral, then dry it in an oven at 100°C for 3 hours, and then place it in a muffle furnace and calcine it under argon protection at a temperature of 600°C, a heating rate of 12°C / min, and a calcination time of 5 hours. The product is cooled to room temperature, filtered, washed, and dried in an oven at 100°C for 2 hours to obtain a thermal conductive material V with a coating thickness of 0.08 μm.

[0123] The raw material composition of the thermal conductive silicone gasket is shown in Table 5:

[0124] Table 5 Raw material composition of thermal conductive silicone gasket in Example 5

[0125]

[0126]

[0127] The preparation steps of thermal conductive silicone gasket are as follows:

[0128] (1) Add vinyl silicone oil, thermal conductive filler, thermal conductive material V, temperature resistant agent and n-decyl trimethylsiloxane into a reaction kettle, stir at high speed at 40° C. for 1.5 h, then add hexamethyldisilazane, stir at high speed for 1 h, heat to 150° C. and stir at low speed for 2.5 h, cool to 40° C., add inhibitor and hydrogen-containing silicone oil, stir under vacuum for 30 min, then add catalyst, stir under vacuum for 30 min, and obtain thermal conductive silicone gasket material;

[0129] (2) Turn on the thermal calendering line, set the temperature of each section of the tunnel furnace from front to back to 80°C, 100°C, 115°C, 135°C and 115°C, adjust the calendering thickness to 1 mm, and after the tunnel furnace reaches the set temperature, put the high temperature aging resistant thermal conductive gasket material into the calendering line trough, and calender at a speed of 0.5 m / min to obtain a thermal conductive silicone gasket.

[0130] Comparative Example 1

[0131] This comparative example prepares a thermally conductive silicone gasket, which differs from Example 1 only in that the thermally conductive material I is replaced with diamond powder of the same mass and particle size of 50 μm, and the preparation method is the same as Example 1.

[0132] Comparative Example 2

[0133] This comparative example prepares a thermally conductive silicone gasket, which differs from Example 2 only in that 30 parts by mass of thermally conductive material II are replaced by 29.7 parts by mass of diamond powder with a particle size of 40 μm and 0.3 parts by mass of γ-Fe2O3 with a particle size of 0.08 μm. The preparation method is the same as Example 2.

[0134] Performance Testing

[0135] The thermally conductive silicone gaskets prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests, and the test items included appearance, thermal conductivity, hardness, and high temperature aging performance. The test methods and standards were as follows:

[0136] 1. Appearance: Observe whether the surface of the gasket is sticky, powdery, brittle, and whether it can be broken when folded in half;

[0137] 2. Thermal conductivity: Tested in accordance with ASTM 5470 "Standard Test Method for Thermal Conductivity of Thermally Conductive Electrical Insulating Materials";

[0138] 3. Hardness: Test according to ASTM D2240 "Standard Test Method for Durometer Hardness";

[0139] 4. High temperature aging performance: The prepared thermal conductive silicone gasket was placed in a precision oven and aged at 210°C for 1000 hours. It was then taken out and cooled to room temperature. The hardness and thermal conductivity were tested and recorded.

[0140] Figure 1 This is a photo of the thermally conductive silicone gasket prepared in Example 1 before aging; Figure 2 This is a photo of the thermal conductive silicone gasket prepared in Example 1 after aging and folding test. Figure 3 A photo was taken of the thermally conductive silicone gasket prepared in Comparative Example 1 after aging and folding test; Figure 4 This is a photo of the thermally conductive silicone gasket prepared in Example 2 before aging; Figure 5 The photo was taken for the thermally conductive silicone gasket prepared in Example 2 after aging and folding test. Figure 6 A photo was taken of the thermally conductive silicone gasket prepared in Comparative Example 2 after aging and folding test; Figure 1-6 It can be seen that the thermally conductive silicone gaskets prepared in Examples 1 and 2 can be folded continuously before aging, and can also be folded continuously after aging at 210°C for 1000 hours, indicating that the thermally conductive silicone gaskets provided by the present invention have excellent high temperature aging resistance, and the long-term working temperature can reach above 200°C; the thermally conductive silicone gaskets prepared in Comparative Examples 1 and 2 do not adopt the formula provided by the present invention, and do not use the thermally conductive material provided by the present invention. The thermally conductive silicone gaskets crack when folded after aging, and have poor high temperature aging resistance, indicating that the thermally conductive material provided by the present invention is beneficial to improving the high temperature aging resistance of the thermally conductive silicone gasket, and diamond and γ-Fe2O3 have a synergistic high temperature resistance effect, which cannot function when only one is added or the two materials are added separately.

[0141] Table 6 Performance test results of thermally conductive silicone gaskets prepared in Examples 1-5 and Comparative Examples 1-2

[0142]

[0143] Table 6 is the performance test results of the thermally conductive silicone gaskets prepared in Examples 1-5 and Comparative Examples 1-2. It can be seen from Table 6 that the surface of the thermally conductive silicone gaskets prepared in Examples 1-5 is sticky before aging, with a thermal conductivity of 14.4-17.2 W / mk and a hardness of 53-62. After aging, the surface is still sticky, with a thermal conductivity of 14.0-16.8 W / mk and a hardness of 59-67. It can be seen that the performance change of the thermally conductive silicone gasket before and after aging is small, and the thermally conductive silicone gasket before and after aging is not easy to break when folded in half, indicating that the thermally conductive silicone gasket provided by the present invention has excellent thermal conductivity and high temperature aging resistance, and can meet the application requirements of electronic components. In addition, the surface viscosity of the thermally conductive silicone gasket ensures good contact between the thermally conductive silicone gasket and the surface of the component, thereby improving the heat conduction efficiency, helping the electronic components to dissipate heat faster, and also preventing the gasket from moving or falling off during use, playing a role in sealing and reducing oxidation of electronic components.

[0144] After aging, the surface stickiness of the thermally conductive silicone gaskets prepared in Comparative Examples 1 and 2 disappears, they crack when folded, and the thermal conductivity coefficient drops significantly, the hardness increases significantly, and the performance difference before and after aging is large, indicating that the high temperature aging resistance of the thermally conductive silicone gasket is poor.

Claims

1. A thermally conductive material, characterized in that: The heat-conducting material is diamond coated with γ-Fe2O3.

2. The thermally conductive material according to claim 1, characterized in that: In the γ-Fe2O3 coated diamond, the particle size of the diamond is 2-100 μm; And / or, the thickness of the γ-Fe2O3 coating layer is 0.01-0.5 μm.

3. The thermally conductive material according to claim 1 or 2, characterized in that: The thermally conductive material comprises the following raw materials: Diamond, iron salts, acid, surfactant, alcohol and alkali; Preferably, the surfactant is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol; Preferably, the iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric stearate and ferric acetate.

4. The thermally conductive material according to claim 3, characterized in that: The mass ratio of the diamond, iron salt, surfactant and alcohol is (10-30):(55-75):(0.3-1.5):100; and / or, the solute concentration of the acid solution is 2-5 mol / L; And / or, the solute concentration of the alkali solution is 20-30wt%.

5. The method for preparing the thermally conductive material according to claim 3 or 4, characterized in that: The following steps are involved: S1, soaking the diamond in acid solution to obtain activated diamond; S2, dispersing iron salt in alcohol, adding the activated diamond and surfactant, and dropping alkali solution for precipitation; S3, collecting the precipitate, calcining, and obtaining the thermal conductive material.

6. A thermally conductive silicone gasket, characterized in that: The preparation material comprises the following raw materials, in parts by mass: 90-110 parts of vinyl silicone oil, 5-25 parts of hydrogenated silicone oil, 2000-3500 parts of thermal conductive filler, 0.5-5 parts of temperature resistant agent, 0.5-10 parts of coupling aid, 0.1-5 parts of catalyst, 0.01-2 parts of inhibitor, and 10-100 parts of the thermal conductive material according to any one of claims 1 to 4.

7. The thermally conductive silicone gasket according to claim 6, characterized in that: The hydrogen content of the hydrogen-containing silicone oil is 0.05-0.3wt%; and / or, the content of siloxane D3-D20 in the vinyl silicone oil and the hydrogen-containing silicone oil is less than 100 ppm; And / or, the particle size of the thermal conductive filler is three-graded: 0.3-1.5 μm, 3-10 μm and 40-150 μm.

8. The thermally conductive silicone gasket according to claim 6, characterized in that: The thermally conductive silicone gasket is prepared by a method comprising the following steps: The vinyl silicone oil, thermal conductive filler, thermal conductive material, temperature resistant agent and coupling aid are mixed at 30-160°C, cooled to 40°C or below, inhibitor and hydrogen-containing silicone oil are added first, and then a catalyst is added to obtain a mixture, and the mixture is calendered to obtain the thermal conductive silicone gasket.

9. The thermally conductive silicone gasket according to claim 8, characterized in that: The calendering temperature is 70-160°C; And / or, the calendering speed is 0.3-2 m / min.

10. Use of the thermally conductive silicone gasket according to any one of claims 6 to 9 in electronic components.